Covid-19 dan Krisis Industri Kreatif dalam Kapitalisme Digital: Komodifi kasi Pekerja Media Digital dalam Kerangka Data as Labor - Hendar Putranto (Center for Philosophy and Ethics, 2020)
Entering 2020, the Covid-19 epidemic struck the lives of all people across borders of nation-states mercilessly and this triggered a global economic recession. Pandemic brought various unforeseen crises, including for Creative Industry workers. Although the last two decades show a positive trend of Creative Industry’s financial contribution for Indonesia's GDP, but, long before the outbreak of the Pandemic, the seeds of the crisis of the Creative Industries have been around for a long time, starting from the transition phase of the era of Industrial Capitalism to Digital Capitalism. Using the approach of the Analysis of Political Economy of the Media, the author will show the genealogy of the crisis by outlining the conceptual dimension of 'structural violence' refering to the Structural Theory of Galtung's Cultural Imperialism (1971). A brief history of the term Digital Capitalism is also discussed in order to obtain a more comprehensive understanding of the crisis. Furthermore, a number of political economy issues that emerged in Digital Capitalism were identified to indicate the locus problematicus of the ongoing crisis. The core argument of this paper will show why the problems of political economy concerning the dualism of Data as Capital and Data as Labor are serious problems in Digital Capitalism, which escapes the attention of the public. The Author offers solution by combining a more equitable pro-Structural input from Galtung analysis, Marxist perspectives, and the collective pro-agency approach from Arrieta-Ibarra, et al. (2018). Analysis of the problem of commodification of Digital Media Workers in the framework of Data as Labor is expected to increase the reader's awareness that the relationship of inequality and exploitation of workers in the era of Industrial Capitalism actually continues in Digital Capitalism when Big Data becomes the logic of new capital accumulation (within the framework of Data as Capital) with The Big Five Internet Corporations as the responsible actors. When Covid-19 hit, material conditions and the survival of creative industry workers as free labor were made even worse.